Citrus Viroids: Symptom Expression and Effect on Vegetative Growth and Yield of Clementine Trees Grafted on Trifoliate Orange - Verniere, C.; Perrier, Xavier; Dubois, C.; Dubois, A.; Botella, L.; Chabrier, C.; Bove, J. M.; Durán-Vila, Núria (The American Phytopathological Society (APS), 2022)
Citrus are natural hosts of five viroid species: Citrus exocortis viroid (CEVd), Citrus bent leaf viroid (CBLVd), Hop stunt viroid (HSVd), Citrus viroid III (CVd-III), and Citrus viroid IV (CVd-IV). CEVd and specific sequence variants of HSVd are the causal agents of the wellknown diseases of citrus, exocortis and cachexia. Other viroids have been found to induce different degrees of stunting. Since commercial citrus trees are commonly infected with mixtures of these viroids, only limited information is available on their effect in species other than Etrog citron. A field assay was conducted to establish the effect of each viroid on Commune clementine trees grafted on Pomeroy trifoliate orange. Infected trees were periodically monitored over a 12-year period (1990 to 2002) for symptom expression, growth, and fruit yield. Only CEVd caused bark scaling on the trifoliate orange rootstock and marked dwarfing, both characteristic of exocortis disease as initially described. In addition, very conspicuous bumps were observed in the wood of the rootstock after removing the bark. Only those HSVd variants, previously characterized as pathogenic in several cachexia-sensitive species, induced pits and gum deposits characteristic of this disease in the clementine scion. Bark cracking symptoms on the trifoliate orange rootstock were also observed. They were associated with CVd-IV, HSVd, or CEVd infection, but in the latter, they were only clearly observed in trees that showed mild scaling. Other abnormalities (deep pits, crests, and gummy pits) were not associated with viroid infection. No specific symptoms resulted from infection with CBLVd and CVd-III. HSVd, CVdIV, and CBLVd had little or no effect in growth and yield, whereas CEVd and CVd-III caused a significant reduction of growth and yield, which became more pronounced over time with CEVd infection. Yield reduction was associated mainly with loss of production of large fruits. In general, there was a good correlation between reduction in vegetative growth and yield.